Immunocytochemistry Analysis of HepG2 Cell 3D Culture Encapsulated as Spheroids in Alginate Beads - Miranda, Raul Ghiraldelli; Ferraz, Elisa Raquel Anastácio; Pereira, Lilian Cristina [UNESP]; Dorta, Daniel Junqueira [UNESP] (Springer Nature, 2021)
3D Cell culture is an alternative to animal use in many drug development and toxicity studies. The 3D cell culture can mimic and reproduce the original tissue microenvironment, morphology, and mechanical and physiological characteristics, to provide a more realistic and reliable response as compared to two-dimensional cultures. 3D cell culture encapsulated in alginate beads is a very simple and relatively inexpensive tool that is easy to handle and to maintain. The alginate beads function as a scaffold that imprisons cells and allows 3D cell growth, to generate spheroids that can have greater genic expression and cell–cell communication as a nano or microtissue. The HepG2 cell line is a human hepatocellular carcinoma cell derivative. HepG2 cells preserve several of the characteristics of hepatocytes and are therefore often used in toxicity studies. Here, we describe HepG2 cell encapsulation in alginate beads and analyze the resulting spheroids formed within the alginate beads by immunocytochemistry, by staining a certain structure with a specific antibody coupled with a fluorophore. This method preserves the beads and enables cell analysis by confocal microscopy.
Keywords: 3D culture; Alginate beads; Confocal microscopy; Encapsulation; HepG2; Immunocytochemistry